Honduras : Joint Staff Advisory Note on the Poverty Reduction Strategy Paper Second Annual Progress Report. (IMF Staff Country Reports; Country Report, 2005)
The Joint Staff Advisory Note on Honduras's Poverty Reduction Strategy Paper Second Annual Progress Report is presented. The framework, which is consistent with the government's economic program being supported by the Poverty Reduction and Growth Facility arrangement, aims at achieving sustainable growth, reducing poverty, and maintaining macroeconomic and financial stability. The strategy involves continuing structural reforms and prudent macroeconomic policies. Reforms to boost growth focus on strengthening the development of human capital and basic infrastructure, improving the environment for private sector development, and using international trade agreements.